2012
DOI: 10.1161/atvbaha.112.251314
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid Dendritic Cells Play a Key Role in Promoting Atherosclerosis in Apolipoprotein E–Deficient Mice

Abstract: Objective-Clinical studies have identified that reduced numbers of circulating plasmacytoid dendritic cells (pDCs) act as a predictor of cardiovascular events in coronary artery disease and that pDCs are detectable in the shoulder region of human atherosclerotic plaques, where rupture is most likely to occur. Results from animal models are controversial, with pDCs seen to inhibit or promote lesion development depending on the experimental settings. Here, we investigated the role of pDCs in atherosclerosis in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 57 publications
1
102
4
1
Order By: Relevance
“…pDCs isolated from atherosclerotic mice suppressed CD4 + T-cell proliferation in an indoleamine-2,3-dioxygenasedependent manner, suggestive of an atheroprotective role for pDCs in atherosclerosis. 53 In contrast to our study, Döring and colleagues 28 and MacRitchie and colleagues, 54 as well, reported significantly decreased diet-induced lesion formation in the aortic root and the aorta of pDC-depleted ApoE −/− mice, whereas plaques showed a more stable phenotype. Both groups investigated the impact of pDC depletion by use of the PDCA-1 depletion antibody on early lesion development (4 weeks of high-fat diet feeding).…”
Section: A Functional Role For Plasmacytoid Dcs In Atherosclerosiscontrasting
confidence: 95%
See 2 more Smart Citations
“…pDCs isolated from atherosclerotic mice suppressed CD4 + T-cell proliferation in an indoleamine-2,3-dioxygenasedependent manner, suggestive of an atheroprotective role for pDCs in atherosclerosis. 53 In contrast to our study, Döring and colleagues 28 and MacRitchie and colleagues, 54 as well, reported significantly decreased diet-induced lesion formation in the aortic root and the aorta of pDC-depleted ApoE −/− mice, whereas plaques showed a more stable phenotype. Both groups investigated the impact of pDC depletion by use of the PDCA-1 depletion antibody on early lesion development (4 weeks of high-fat diet feeding).…”
Section: A Functional Role For Plasmacytoid Dcs In Atherosclerosiscontrasting
confidence: 95%
“…In line with this, Döring and colleagues 28 showed that sorted aortic pDCs from hyperlipidemic mice, ex vivo primed, were capable of triggering T-cell stimulation in vivo. Finally, baseline IFN-α levels were below detection levels or not affected by pDCs in our study and the study of MacRitchie and coworkers, 53,54 whereas Döring and colleagues 28 demonstrated elevated IFN-α levels in plaque (mRNA) and serum in high-fat diet-fed ApoE −/− mice, being reduced after pDC depletion. It must be noted that these groups used different methodologies, such as the use of the depletion antibody, administration regimen, and mouse models.…”
Section: A Functional Role For Plasmacytoid Dcs In Atherosclerosiscontrasting
confidence: 46%
See 1 more Smart Citation
“…Thus, deletion of MyD88 in CD11c-expressing macrophages in atherosclerotic lesions (13) could potentially decrease lesional inflammation and thus suppress atherosclerosis. If this were the case, the data herein would indicate that the proatherogenic effects of MyD88 depletion in CD11c + DCs are dominant over the potentially antiatherogenic effects of MyD88 depletion in CD11c + macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the net effect of DC-mediated T cell activation on atherogenesis would depend on the type(s) of T cells that is activated in the environmental and antigen context of atherosclerosis. Most mouse studies in which DCs have been depleted or disabled show a decrease in atherosclerosis, suggesting that a major role of DCs is activation of proatherogenic T effector (Teff) cells (10)(11)(12)(13). On the other hand, a recent study showed that deletion of Flt3, which results in defective development of conventional DCs, a decrease in lesional CD103 + DCs, and a systemic decrease in Tregs, is associated with an increase in atherosclerosis (14).…”
Section: Introductionmentioning
confidence: 99%